RELATIONSHIP BETWEEN GUIDANCE AND COUNSELING INFORMATION SERVICES AND LIFE SKILLS AMONG SELECTED SECONDARY SCHOOLS IN MUDUUMA SUB-COUNTY, MPIGI DISTRICT. A CROSS-SECTIONAL STUDY. - Zawedde , Josephine; Kiyingi, Pio Frank (SJ Insights, 2025)
Background The perception of guidance and counseling services in primary schools varies across European countries due to differing educational systems and cultural contexts. The study aims to assess the relationship between guidance and counseling information services and life skills among selected secondary schools in Muduuma Sub-County, Mpigi District. Methodology A cross-sectional study utilizing both qualitative and quantitative research methods. Qualitative component involved obtaining graphs, and charts. Simple Random Sampling and Purposive Sampling were used. Results (53.7%) of the students were in the boarding section while (46.3%) were in the day section. Participants reported a mean familiarity score of M = 3.24 (SD = 1.013) with the guidance and counseling information services provided at the secondary schools. The mean score for participants' belief in the value of the guidance and counseling information services for personal development was M = 3.83 (SD = 0.940). Participants' satisfaction with the accessibility and availability of guidance and counseling information at the school yielded a mean score of M = 3.56 (SD = 1.353). The mean score for participants' perception of the guidance and counseling information services' coverage of different aspects of life skills development was M = 3.54 (SD = 0.945). The mean score for participants' perception of support for overall well-being and personal development by guidance and counseling information services was M = 3.46 (SD = 0.996). Conclusion Guidance and counseling information provided at school helps students not only improve their academic performance but also their social life as per their relationships. Recommendations The Ministry of Gender, Labour, and Social Development and the Ministries of Education collaborate to enhance the quality of guidance and counseling information services in secondary schools.